Unclear Public Policy: The Real Barrier in Recognizing Foreign Arbitration Awards? - Sugianto, Fajar; Athina Indradewi, Astrid; Antonius Sanjaya, Robin; Yamamoto, Atsuko (Universitas Negeri Semarang, 2025)
In Indonesia, a foreign arbitral award refers to a decision issued by an arbitration institution or arbitrator outside the country or recognized as such under Indonesian law. This classification reflects Indonesia’s adherence to the principle of territoriality in distinguishing arbitration awards as